Inhibition of Host Deoxyribonucleic Acid Synthesis by T4 Bacteriophage in the Absence of Protein Synthesis - Duckworth, Donna Hardy (1971)
The requirement for phage protein synthesis for the inhibition of host deoxyribonucleic acid synthesis has been investigated by using a phage mutant unable to catalyze the production of any phage deoxyribonucleic acid. It has been concluded that the major pathway whereby phage inhibit host syntheses requires protein synthesis. The inhibition of host syntheses by phage ghosts is not affected by inhibitors of protein synthesis.